Enhancing Students’ Self-Disclosure Through Assertive Training: Evidence from a Group Counseling Intervention - Abu Bakar, Abu Yazid; Bariyyah, Khairul; Andrianie, Santy; Setyorini, Setyorini; Ariyanto, Restu Dwi; Soejanto, Laily Tiarani; Bil Humaydah, Dzata Inasah (Buletin Konseling Inovatif, 2026)
Self disclosure is a critical component of students’ social and emotional development; however, many students experience difficulties in expressing their thoughts and feelings openly, which may hinder interpersonal relationships and psychological well-being. This study aims to examine the effectiveness of group counseling using assertive training techniques in enhancing students’ self-disclosure. A quantitative approach with a pre-experimental one-group pre-test–post-test design was employed. The participants consisted of five junior high school students identified as having low self-disclosure levels through purposive sampling. Data were collected using a self-disclosure scale and analyzed using descriptive statistics, paired samples t-test, effect size (Cohen’s d), Wilcoxon signed-rank test, and gain score analysis. The data showed that the post-test average for self-disclosure significantly jumped to 94.00 (SD = 2.74) compared to the pre-test average of 58.20 (SD = 1.92). According to the paired samples t-test, the difference was statistically significant (t(4) = -23.403, p <.001). The very large effect size further corroborates this finding (d = -10.466). The gain score analysis also revealed that every individual has made some progress, the mean increment being 35.80 points. At the same time, the study showed that group counseling with assertive training is a very effective way of increasing students' self-disclosure, not only in theory but in practice as well. Moreover, the study reinforces the idea of skill-based counseling as a means to enhance students' communication abilities and to promote more inclusive and responsive school settings.